(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the importance, relevance and effectiveness of spiritual and educational work in the process of transforming New Uzbekistan into a country free of corruption. The national and spiritual bases of the fight against corruption and the essence of the ongoing reforms in the country are also highlighted.